2015
DOI: 10.1177/0194599814566179
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Care for Subjective Tinnitus in Relation to Patient Satisfaction

Abstract: Given that the variability among provider recommendations, the high overall mean of tinnitus-related charges, and patient satisfaction was not related to costs, further research is needed examining patient preference in the treatment of tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 36 publications
0
36
1
Order By: Relevance
“…An economic study undertaken in the United States in 2015 gave broadly similar figures to the United Kingdom study, estimating healthcare costs at US$660 per patient per year (Goldstein et al, 2015). A Dutch study (Maes et al, 2013) suggested even higher figures with an estimated mean annual tinnitus-related cost per patient of €1544, though this study made the assumption that all patients with tinnitus were actively seeking help for their condition and may therefore be an overestimate.…”
Section: Patient and Provider Perspectives On Tinnitus Treatment Optionsmentioning
confidence: 87%
“…An economic study undertaken in the United States in 2015 gave broadly similar figures to the United Kingdom study, estimating healthcare costs at US$660 per patient per year (Goldstein et al, 2015). A Dutch study (Maes et al, 2013) suggested even higher figures with an estimated mean annual tinnitus-related cost per patient of €1544, though this study made the assumption that all patients with tinnitus were actively seeking help for their condition and may therefore be an overestimate.…”
Section: Patient and Provider Perspectives On Tinnitus Treatment Optionsmentioning
confidence: 87%
“…Tinnitus management requires a multidisciplinary approach due to the heterogeneity of tinnitus and the absence of a cure (Cima et al, 2020). The average cost of tinnitus treatment per patient per year is approximately USD 660 in the United States (USA) (Goldstein et al, 2015), GBP 717 in the United Kingdom (UK) (Stockdale et al, 2017), and EUR 1,544 in the Netherlands (Maes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding use of healthcare resources for tinnitus, published studies modelling populationbased health care costs have typically used the number of tinnitus-related general practitioner visits and/or hospital visits as a basis for cost estimates of the burden on healthcare resources, and this information has been obtained retrospectively from clinical records (Goldstein et al, 2015;Maes et al, 2013). To our knowledge, there has been no published population survey asking participants a question on use of healthcare resources for tinnitus.…”
Section: Description Of the Original Source Itemsmentioning
confidence: 99%
“…In the absence of an efficient and effective healthcare system such patients can often make repeat appointments, creating a 'revolving door' pattern of healthcare (McFerran et al, 2018). Thus, a clinically significant tinnitus, in which people seek medical help, imposes personnel and financial resource burden on the healthcare system (Goldstein et al, 2015;Maes et al, 2013;Stockdale et al, 2017). This information can easily be captured by a question about the number of appointments for tinnitus-related problems in the past year.…”
Section: Introductionmentioning
confidence: 99%